The World Drug Policy Problem. An Interview with José Ramos-Horta - José Ramos-Horta; Khalid Tinasti (Revue Internationale de Politique de Développement)
José Ramos-Horta is a former president of Timor-Leste, a Nobel Peace Prize laureate and a current member of the Global Commission on Drug Policy (GCDP). Khalid Tinasti, one of the guest editors of this Thematic Issue, interviewed José Ramos-Horta to gain insight into his views and analyses of drug control policy. They discuss his experience as one of the drafters of the Constitution and criminal justice responses in Timor-Leste, and his role as the UN Secretary-General’s Special Representative and head of the United Nations Integrated Peacebuilding Office in Guinea-Bissau (UNIOGBIS) at a time when the country was labelled a ‘narco-state’. Khalid Tinasti also asked him about his views on the future of the drug market in the context of a growing drug policy divide between countries that enforce a punitive approach to drug use and those now legalising cannabis and other substances for recreational purposes.